Phylogenetic Group Determination of Escherichia coli Isolated from Animals Samples - Fernanda Morcatti Coura; Soraia de Araújo Diniz; Marcos Xavier Silva; Jamili Maria Suhet Mussi; Silvia Minharro Barbosa; Andrey Pereira Lage; Marcos Bryan Heinemann (The Scientific World Journal)
This study analyzes the occurrence and distribution of phylogenetic groups of 391 strains of Escherichia coli isolated from poultry, cattle, and water buffalo. The frequency of the phylogroups was A = 19%, B1 = 57%, B2 = 2.3%, C = 4.6%, D = 2.8%, E = 11%, and F = 3.3%. Phylogroups A (P<0.001) and F (P=0.018) were associated with E. coli strains isolated from poultry, phylogroups B1 (P<0.001) and E (P=0.002) were associated with E. coli isolated from cattle, and phylogroups B2 (P=0.003) and D (P=0.017) were associated with E. coli isolated from water buffalo. This report demonstrated that some phylogroups are associated with the host analyzed and the results provide knowledge of the phylogenetic composition of E. coli from domestic animals.